2021
DOI: 10.11646/zootaxa.4948.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Two new Canthocamptidae (Copepoda, Harpacticoida) from sponges of the Kara and Laptev Seas

Abstract: We studied copepods washed off the sponges from two Arctic seas: the Kara and the Laptev. We found new species in families Miraciidae, Canthocamptidae Brady, 1880, Argestidae, and Ectinosomatidae. We describe two new species of the Canthocamptidae Brady, 1880. Heteropsyllus spongiophilus sp. nov. from the Kara Sea, differs from its congeners in the armament of the swimming legs and the maxilliped. Mesopsyllus glacialis sp. nov. from the Laptev Sea, can be distinguished by the legs armament, its sexual dimorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 425 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…1.0. Novikov & Sharafutdinova, 2021 from the Laptev Sea and Mesochra pontica Marcus, 1965 from the Black Sea were used as outgroups. For comparison with other freshwater genera, we included the following species in the analysis: from Udmurtia (European part of Russia): Attheyella (A.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1.0. Novikov & Sharafutdinova, 2021 from the Laptev Sea and Mesochra pontica Marcus, 1965 from the Black Sea were used as outgroups. For comparison with other freshwater genera, we included the following species in the analysis: from Udmurtia (European part of Russia): Attheyella (A.)…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to other genera of cantocamptids, the genus Canthocamptus is characterised by a very unusual pore structure. In general, the marine species of canthocamptids have a typical structure (Novikov & Sharafutdinova 2021); in this case, each somite carries one unpaired dorsal pore, one pair of lateral pores and one pair of ventral pores. However, Canthocamptus spp.…”
Section: Female Endopodmentioning
confidence: 99%
“…In the Atlantic, it is limited to the eastern part and has not been encountered off the coast of America. Also, the genus is quite common in the seas of the Arctic Ocean, from where 4 species are described together with a new species [Smirnov, 1946;Kornev, Chertoprud, 2008;Novikov, Sharafutdinova, 2021]. In the Pacific Ocean, the distribution is unknown due to low knowledge, one species is known near Jeju Island (South Korea) [Nam, Lee, 2006].…”
Section: Subclass Copepoda H Milne-edwards 1840mentioning
confidence: 99%
“…Kornev & Chertoprud [2008] separated the genus into a monotypic family Heteropsyllidae Kornev et Chertoprud, 2008. Following that, some authors still indicated this genus as part of the Canthocamptidae family [George, 2013;Garlitska et al, 2019], including the recently described species Heteropsyllus spongiophilus Novikov et Sharafutdinova, 2021. The authors indicated the similarity of Heteropsyllus in some characteristics to Hemimesochrinae; however, they do not indicate the exact position [Novikov, Sharafutdinova, 2021].…”
Section: Introductionmentioning
confidence: 99%